"I Am Normal": Claiming Normalcy in Christian‐Identified HIV‐Infected Adolescent and Emerging Adult Males. (November 2016) - Smith, Sharon T.; Dawson‐Rose, Carol; Blanchard, Jennifer; Kools, Susan; Butler, Derrick
Abstract : N/A: Acquiring HIV in adolescence and young adulthood, when development of self‐identity, personal values, and life purpose are central, is challenging. The purpose of our study was to explore the spiritual needs of young people with HIV, learning strategies they used to cope with the disease. A constructivist grounded theory study was conducted. A purposive sample of 21 Christian‐identified HIV‐infected males was interviewed. The iterative coding phases of grounded theory, including open, axial, selective, and theoretical, were used to analyze data, and a theory of claiming normalcy with HIV was generated. We present the salient theme "I am normal, " describing young people's attempts to function the same as peers despite requiring daily treatment. Conditions associated with feelings of normalcy included disclosure status, stigma experiences, support, and health status. Participants sought meaning in the disease, ongoing social engagement, and self‐belief. Reinforcing feelings of normalcy may help young people cope with HIV.